Análise comparativa de fatores associados à respostas positivas em ciclos de reprodução assistida - Resner, Danieli Aparecida (2025)
Infertility is defined as the difficulty in getting pregnant after 12 months of trying without using protection. It is estimated that the problem may affect 8 to 12% of couples of childbearing age. Considering its high prevalence, infertility has become a significant global public health problem. Thus, the search for Assisted Human Reproduction Techniques (ARTs) has become an alternative for couples who have difficulty getting pregnant naturally. In Brazil, most assisted reproduction services are provided by the private sector, since in a large part of the country, there is still no coverage by the Unified Health System (SUS). The present study aimed to collect data from the medical records of patients who underwent their first assisted reproduction cycle at a fertility clinic in Francisco Beltrão, Paraná. This is a retrospective, observational, and descriptive study that analyzes the medical records of couples who underwent ART treatment from 2016 to 2023. The sample consisted of 95 women who tried some method to get pregnant for the first time. Data on parity, technique used, outcome, and hormonal profile were entered into Microsoft Excel spreadsheets and analyzed in the Jasp program, v. 19.3. The chi square test was used for the analyses, in addition to analysis of variance (ANOVA) or Kruskal-Wallis. The mean age was 35.02 ± 4.40 years. The mean age of the spouse was higher (38.18 ± 6.51). Regarding parity, 64 women were nulliparous and 19 had already had a previous pregnancy. Regarding the type of treatment, 38 patients underwent intracytoplasmic sperm insemination, followed by 21 patients who underwent intrauterine insemination and in vitro fertilization, respectively. The outcome variable showed 66 with a negative outcome in the first cycle, 22 became pregnant and 7 miscarried. Regarding the outcome, 30.4% of the cases had Prolactin and Estradiol as significant predictors. Future studies, with larger samples and including interactions between types of treatment and hormone levels analyzed here may increase the chances of success of the outcomes under analysis.